Regional Leadership Strategy in Accelerating the Handling of COVID-19 in Indonesia: A Case Study in DKI Jakarta Province, East Java, Central Java, South Sulawesi and West Java) - Rahmawati, Noor Indah; Winahyuningsih, Panca; Lusianti, Dina (KnE Social Sciences, 2021)
Currently, the world in general and Indonesia in particular are being hit by the COVID-19 pandemic. As the highest leader at the provincial level, the governor has a big role in handling COVID-19. The purpose of this study was to examine the leadership strategy of regional heads in handling COVID-19 in Indonesia. The sample in this study consisted of the 5 provinces with the largest positive cases of COVID-19 in Indonesia, namely DKI Jakarta, East Java, Central Java, South Sulawesi and West Java. A qualitative approach was used with descriptive analysis techniques. Secondary data techniques included a literature study. The results of this study indicated that 1) the governors of DKI Jakarta, East Java, Central Java, South Sulawesi and West Java have implemented the same leadership strategy, namely forming a task force, establishing a state of emergency and setting regulations to accelerate the handling of COVID-19. 2) The number of additional positive cases in the five provinces still shows an increase on average. 3) The number of recovered patients in the five provinces shows an increase on average. 4) The number of patients who died in the five provinces showed fluctuation. Keywords: leadership, regional head, COVID-19